Analisis Pemahaman Siswa dalam Menyelesaikan Soal Cerita pada Materi Aritmetika Sosial Berdasarkan Teori Apos di SMP Negeri 1 Wanokaka - Boku, Rosanti Rada; Lubur, Dorothea N.L; Napu, Timotius Woda; Lede, Yulius Keremata (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze students' understanding in solving story problems on social arithmetic based on the stages of the APOS Theory (Action, Process, Object, and Schema). The study used a qualitative approach with descriptive methods. The subjects were seventh-grade students of SMP Negeri 1 Wanokaka who were selected purposively based on the results of comprehension ability tests. Data collection was carried out through story problem tests, in-depth interviews, and documentation. Data analysis used the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawing, while data validity was obtained through technical triangulation. The results showed that students' understanding abilities varied at each APOS stage. At the Action stage, students were able to perform routine calculations, but still had difficulty in solving complex story problems. At the Process stage, students began to be able to model problems into mathematical forms, but were not consistent. Most students had not yet reached the Object and Schema stages, so they were unable to fully understand the concept of social arithmetic or connect concepts in problem solving. The most dominant errors occurred in the modeling process from the Action to the Process stage. Thus, learning needs to be designed to facilitate the development of students' conceptual understanding gradually according to the stages of the APOS Theory.